New generation of drug delivery systems based on ginsenoside Rh2-, Lysine- and Arginine-treated highly porous graphene for improving anticancer activity - Zare-Zardini, H.; Taheri-Kafrani, A.; Amiri, A.; Bordbar, A.K. (Nature Publishing Group, 2018)
In this study, Rh2-treated graphene oxide (GO-Rh2), lysine-treated highly porous graphene (Gr-Lys), arginine-treated Gr (Gr-Arg), Rh2-treated Gr-Lys (Gr-Lys-Rh2) and Rh2-treated Gr-Arg (Gr-Arg-Rh2) were synthesized. MTT assay was used for evaluation of cytotoxicity of samples on ovarian cancer (OVCAR3), breast cancer (MDA-MB), Human melanoma (A375) and human mesenchymal stem cells (MSCs) cell lines. The percentage of apoptotic cells was determined by terminal deoxynucleotidyl transferase-mediated dUTP nick-end labeling (TUNEL) assay. The hemolysis and blood coagulation activity of nanostructures were performed. Interestingly, Gr-Arg, Gr-Lys, Gr-Arg-Rh2, and Gr-Lys-Rh2 were more active against cancer cell lines in comparison with their cytotoxic activity against normal cell lines (MSCs) with IC50 values higher than 100 μg/ml. The results of TUNEL assay indicates a significant increase in the rates of TUNEL positive cells by increasing the concentrations of nanomaterials. Results were also shown that aggregation and changes of RBCs morphology were occurred in the presence of GO, GO-Rh2, Gr-Arg, Gr-Lys, Gr-Arg-Rh2, and Gr-Lys-Rh2. Note that all the samples had effect on blood coagulation system, especially on PTT. All nanostrucure act as antitumor drug so that binding of drugs to a nostructures is irresolvable and the whole structure enter to the cell as a drug.